2013
DOI: 10.1111/trf.12437
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood progenitor cell collection by two programs for autologous and allogeneic transplantation

Abstract: Spectra-MNC and Spectra-Auto showed distinct features that should be considered on a case-by-case basis. Similar investigations should be undertaken as new collection platforms are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…A moderately negative influence of WBC precount on CD34 + CE2 has previously been observed on both Spectra Optia and Cobe Spectra . A marked drop in CD34 + CE2 with Cobe Spectra MNC was reported by Cooling et al in patients with WBC precounts exceeding 20 × 10 9 /L while Reinhardt et al observed a modest correlation of the CE2 with WBC precount .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A moderately negative influence of WBC precount on CD34 + CE2 has previously been observed on both Spectra Optia and Cobe Spectra . A marked drop in CD34 + CE2 with Cobe Spectra MNC was reported by Cooling et al in patients with WBC precounts exceeding 20 × 10 9 /L while Reinhardt et al observed a modest correlation of the CE2 with WBC precount .…”
Section: Discussionmentioning
confidence: 69%
“…A moderately negative influence of WBC precount on CD34 1 CE2 has previously been observed on both Spectra Optia 6,8 and Cobe Spectra. 6,8,17 A marked drop in CD34 1 8,18 This slight effect could be explained by the two step separations on the Spectra Optia. The more circulating WBC, the faster the chamber will be filled and the more chambers will be collected.…”
Section: Discussionmentioning
confidence: 97%
“…In brief, the freshly obtained samples, which were stained with 7‐AAD and monoclonal antibodies to CD34 and CD45 followed by red blood cell (RBC) lysis, were applied to a single‐platform method. CEs were calculated on the basis of the number of cells that passed through the instrument (CE1) or the TBV of the donors/patients (TBV‐CE), as described previously …”
Section: Methodsmentioning
confidence: 88%
“…The methods and devices of apheresis for PBSC collection have been improved over the past three decades, and several studies have reported distinct characteristics of apheresis devices and programs . Among these, we previously demonstrated that yields and collection efficiencies (CEs) of CD34+ cells were similar between the automated program of the Spectra (Spectra‐Auto, Software Version 6.1, Terumo BCT) and its manual program (Spectra‐MNC); however, numbers of contaminating platelets (PLTs) were greater in the products collected by the Spectra‐MNC compared with the Spectra‐Auto . Recently, the Spectra Optia (Optia, Terumo BCT) has been introduced as a new instrument with an automated program (Optia MNC) for the apheresis collection of PBSCs .…”
mentioning
confidence: 99%
“…Transient thrombocytopenia is an accepted risk of leukapheresis . Reductions of more than 30% from precollection levels are routinely noted.…”
Section: Discussionmentioning
confidence: 99%